Antimicrobial activity of leaf and root extracts of tough lovegrass - Favaretto, Adriana; Tonial, Fabiana; Bertol, Charise Dallazem; Scheffer-Basso, Simone Meredith (Comunicata Scientiae, 2017)
This study aimed to evaluate tough lovegrass leaf and root extracts antimicrobial activity. The extracts (plant material: solvent, 1:10) were prepared by maceration with methanol:water (1:1) during ten days followed by a concentration in a rotary evaporator under reduced pressure. The extracts were resuspended in water containing 1% of dimethylsulfoxide (DMSO) to obtain a final concentration of 100 mg/mL and then filtered through a sterilizing membrane with 0.22μm. The antibacterial activity of the leaf and root extracts were evaluated against pathogenic and phytopathogenic bacteria by agar well diffusion and microdilution broth methods for the minimum inhibitory concentrations (MIC) determination. The antifungal activity of tough lovegrass leaf and root extracts were evaluated by micelial growth inhibition and conidial germination inhibition. The extracts presented low antibacterial activity against Staphylococcus aureus, Staphylococcus epidermidis, and Xanthomonas translucens, but the leaf extracts presented significant antifungal activity against the phytopathogenic fungus Drechslera tritici-repentis. The results support the continuity of the study in improving the effectiveness of the active extract for a possible use in pharmacology and agronomy and in attempting to determine the probable active antimicrobial compound.